Propuesta de un planeamiento estratégico y su influencia en el desempeño laboral de la empresa V & O Builders Consultants S.A.C., Trujillo, 2021 - Saldaña Yañez, María José (2023)
The following study was carried out in the company V & O Builders Consultants S.A.C., dedicated to developing real estate, architecture and engineering activities, with the main objective of proposing strategic planning to improve job performance. For this purpose, a non-experimental design study of descriptive propositional level was developed following the methodology of the sequential model of the strategic process. As part of the study population, 17 key collaborators of the organization were considered, who were consulted about the functioning of the organization through the application of a questionnaire to evaluate the performance of collaborators, identifying that 64.7% of the collaborators considered that the company presented a low performance, being necessary the proposal of a strategic plan for the achievement of its objectives, so strategies were selected to be implemented by the company in order to increase its job performance, previously reproposing the vision and mission of the company according to the established guidelines. Also, a necessary budget of S/ 28,900.00 was calculated to implement the proposal, which when evaluated quantitatively proved to be viable and profitable, with an NPV of S/ 132,058.21 and an IRR of 184.8%, as well as a B/C ratio of 1.05, so it is recommended that the organization consider the results of this study, through the implementation of the strategic plan in the following years.